Combining precision radiotherapy with molecular targeting and immunomodulatory agents: a guideline by the American Society for Radiation Oncology. Issue 5 (May 2018) - Bristow, Robert G; Alexander, Brian; Baumann, Michael; Bratman, Scott V; Brown, J Martin; Camphausen, Kevin; Choyke, Peter; Citrin, Deborah; Contessa, Joseph N; Dicker, Adam; Kirsch, David G; Krause, Mechthild; et al.
Summary: The practice of radiation oncology is primarily based on precise technical delivery of highly conformal, image-guided external beam radiotherapy or brachytherapy. However, systematic research efforts are being made to facilitate individualised radiation dose prescriptions on the basis of gene-expressssion profiles that reflect the radiosensitivity of tumour and normal tissue. This advance in precision radiotherapy should complement those benefits made in precision cancer medicine that use molecularly targeted agents and immunotherapies. The personalisation of cancer therapy, predicated largely on genomic interrogation, is facilitating the selection of therapies that are directed against driver mutations, aberrant cell signalling, tumour microenvironments, and genetic susceptibilities. With the increasing technical power of radiotherapy to safely increase local tumour control for many solid tumours, it is an opportune time to rigorously explore the potential benefits of combining radiotherapy with molecular targeted agents and immunotherapies to increase cancer survival outcomes. This theme provides the basis and foundation for this American Society for Radiation Oncology guideline on combining radiotherapy with molecular targeting and immunotherapy agents.